2021
DOI: 10.1017/ice.2021.457
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuing MRSA and VRE contact precautions: Defining hospital characteristics and infection prevention practices predicting safe de-escalation

Abstract: Objective: To define conditions in which contact precautions can be safely discontinued for methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE). Design: Interrupted time series. Setting: 15 acute-care hospitals. Participants: Inpatients. Intervention: Contact precautions for endemic MRSA and VRE were discontinued in 12 intervention hospitals and continued at 3 nonintervention hospitals. Rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The authors therefore emphasize the importance of network strategies. There is also evidence in the literature that the discontinuation of contact precautions for VRE does not lead to an increase in nosocomial VRE infection rates when well-adapted infection control practices are implemented and the baseline infection rate is low [ 37 ]. In another report, however, cessation of contact precautions and active screening were associated with an increase in VRE infection rates [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors therefore emphasize the importance of network strategies. There is also evidence in the literature that the discontinuation of contact precautions for VRE does not lead to an increase in nosocomial VRE infection rates when well-adapted infection control practices are implemented and the baseline infection rate is low [ 37 ]. In another report, however, cessation of contact precautions and active screening were associated with an increase in VRE infection rates [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, active surveillance for MRSA and VRE may have varied among study facilities, and in 2018, some study facilities discontinued the routine use of contact precautions for MRSA, VRE, and select non-CRE gram-negative pathogens. 19 Differences in application or adherence of active surveillance and contact precautions may affect case ascertainment and change the likelihood of transmission in the room environment. However, these are facility-level approaches, and adjusting for facility in our analysis may account for these differences.…”
Section: Discussionmentioning
confidence: 99%
“… 16 More recently, in an interrupted times-series analysis across 15 acute-care hospitals, the discontinuation of contact precautions resulted in no healthcare-associated infection rate increases. 17 In the recent editorial published in the Journal of Infection Prevention , Wilson and Prieto 18 concluded that the incremental benefit of contact precautions beyond standard precautions for the control of endemic pathogens is lacking and should be subjected to thorough and robust review to better define evidence-based recommendations.…”
Section: The De-escalation Of Contact Precautions In Endemic Settingsmentioning
confidence: 99%